The Whitechapel Art Gallery Centenary Review : 17 articles, 23 artists' pages, 198 images. - Bonaventura, Paul; Breakwell, Ian; Brett, Guy; Brill, Dorothée; Dein, Alan; Drew, Joanna; Francis, Mark; Haythornthwaite, Janeen; Jones, Jonathan; Lampert, Catherine; Levy, Deborah; Lichtenstein, Rachel; et al. (London : Whitechapel Art Gallery, 2001)
Whitechapel Art Gallery London ; Alys, Francis ; Andrews, Michael ; Bomberg, David ; Boyce, Sonia ; Boyd, Arthur ; Burne-Jones, Edward ; Cahun, Claude ; Caro, Anthony ; Caulfield, Patrick ; Celmins, Vija ; Clark, Lygia ; Cornell, Joseph ; Cragg, Tony (Anthony) ; Deacon, Richard ; Doig, Peter ; Flanagan, Barry ; Fontana, Lucio ; Freud, Lucian ; Gormley, Anthony ; Gris, Juan ; Guston, Philip ; Hamilton, Richard ; Hedges, Nick ; Hepworth, Barbara ; Hesse, Eva ; Hockney, David ; Hogarth, William ; Hume, Gary ; Islam, Runa ; Jozan, Ishikawa ; Chen Juzhong ; Kahlo, Frida ; de Kooning, Willem ; Kuitca, Guillermo ; Law, Bob ; Luskacova, Marketa ; Martin, Agnes ; Martin, Kenneth ; Merz, Mario ; Michaux, Henri ; Mondriaan, Piet ; Moore, Henry ; Hamilton Mortimer, John ; Nauman, Bruce ; Nicholson, Ben ; Nolde, Emil ; Rauschenberg, Robert ; Rembrandt ; Riley, Bridget ; Rothko, Mark ; Ryman, Robert ; Sherman, Cindy ; Stubbs, George ; Turner, Joseph Mallord William ; Twombly, Cy ; Uglow, Euan ; Viola, Bill ; Wall, Jeff ; Warhol, Andy ; Yeats, Jack B. ; Wang Zhenpeng
Engels
The Whitechapel Centenary Exhibition, Whitechapel Art Gallery, London, 21 March - 20 May 2001
boek